Transtorno bipolar: características médico-clínicas e das funções executivas - Pereira, Lilian Lopes (2011)
Bipolar disorder (BD) is a severe psychiatric disorder, recurrent, characterized by mood swings and involves neurochemical, cognitive, psychological, functional, family and socioeconomic factors. The literature describes impairments in multiple cognitive domains in patients with BD, which may persist even during periods of euthymia. Executive functions involves cognitive sub-processes, among them self-regulation, mental flexibility, decision making, selective attention and inhibitory control. These functions are impaired in BD, but there is no consensus on the persistence of deficits in euthymia. It is understood that such impairments affect the daily life of the BD patients, and the way they deal with their treatment. In this research, we sought to understand the socio-demographic and clinical characteristics of 41 patients with BD in euthymia, aged between 25 and 60 years, assisted by the Mood Clinic of the Department of Psychiatry, University Hospital of Santa Maria, RS, Brazil, comparing them with a matched group of 41 healthy controls, in order to test for possible differences in executive functions performance, more specifically, mental flexibility and inhibitory control. This is an exploratory, descriptive and case-control study, where the following instruments were used to compare the groups: Wisconsin Card Sorting Test, Stroop Test, and Trail Making Test B. Ethical procedures required for research with human beings were followed. The social-demographic profile, of the group of patients with BD, showed a predominance of female gender, white ethnicity, average age 42.8 years, mean education of 9.4 years of schooling, low occupancy rate in the workplace, most without conjugal relationship, and low family incomes. In the clinical profile of BD patients, the main characteristics were: occurrence of first episode of BD between 21 and 40 years of age; illness duration between 16 and 30 years; at least one psychiatric hospitalization in 80,5% of the patients. There were statistically significant differences between groups in the variables perseverative errors and perseverative responses in WCST, time in TMT, Stroop3, number of errors in the Stroop task, indicating poorer performance of patients with BD, in euthymia, which suggests they present impairments relative to cognitive flexibility and inhibitory control. A marginally significant difference in WCST categories completed variable was observed. Based on the results it is concluded that social life, family and occupational background of BD patients is affected not only by the symptoms of the disease, but also by deficits in cognitive performance. So, it is necessary to take these aspects into account in order to provide a more comprehensive therapeutic approach to patients.